PENERAPAN MODEL CYCLE LEARNING 5E DAN METODE BRAINSTORMING TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS DITINJAU DARI MOTIVASI BELAJAR SISWA PADA MATERI SEGI EMPAT - Vina Triyana (Universitas Pekalongan, 2019)
The purposes of this research were: (1) to understand does Cycle Learning 5E and Brainstorming Methods learning method produce the better mathematics communication capability rather than direct learning method, (2) to understand are students with high motivation have better mathematic communication skills than students with average motivation, are students with average motivation have better mathematic communication skills than students with low motivation, (3) to understand for students with high and average motivation does Cycle Learning 5E and Brainstorming method produce mathematic communication skills better than direct learning and for low motivation students does it produce the same mathematic skills with direct learning. (4) to compare on high with average motivation students, also both the average with low motivation students and high with low motivation students about how Cycle Learning 5E and Brainstorming methods gives them the better mathematic communication skills. This is a quantitative research with pseudo-experiment methods. The population of this research was all the VII grade students of Batang State 1 Junior High School. Sampling method was by Cluster Random Sampling technique. The data collection was using test method and questionnaire method. Data was analyzed by two ways Annova.Result shows that: (1) Cycle Learning 5E and Brainstorming method gives better mathematic communication skills for students rather than direct learning; (2) students with high motivation have better mathematics communication skills than low motivation students, while high and average motivation students have the equal level of mathematic communication skills, and same goes to students with average and low motivation; (3) for all students with high, average and low motivation, the Cycle Learning 5E and Brainstorming method gives better mathematics communication skills than direct learning; (4) on teaching with Cycle Learning 5E and Brainstorming method, high motivation students have better mathematic communication skills rather than low motivation students, while they have equal communication skills with average motivation students. This condition happens also to the average and low motivation students.